2018
DOI: 10.4081/ni.2018.7436
|View full text |Cite
|
Sign up to set email alerts
|

Allgrove syndrome and motor neuron disease

Abstract: Allgrove or triple A syndrome (AS or AAA) is a rare autosomal recessive syndrome with variable phenotype due to mutations in AAAS gene which encodes a protein called ALADIN. Generally, it’s characterized by of adrenal insufficiency in consequence of adrenocorticotropic hormone (ACTH) resistance, besides of achalasia, and alacrimia. Neurologic features are varied and have been the subject of several case reports and reviews. A few cases of Allgrove syndrome with motor neuron disease have been already described.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Triple A syndrome may present with variable neurological findings, such as muscle weakness, hyperreflexia, ataxia, dysarthria, parkinsonism, sensory impairment, and mental retardation ( 2 , 3 ). Several cases of comorbid triple A (Allgrove) syndrome and motor neuron disease have already been reported ( 4 - 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Triple A syndrome may present with variable neurological findings, such as muscle weakness, hyperreflexia, ataxia, dysarthria, parkinsonism, sensory impairment, and mental retardation ( 2 , 3 ). Several cases of comorbid triple A (Allgrove) syndrome and motor neuron disease have already been reported ( 4 - 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…AAAS is located on chromosome 12q13, which is responsible for ALADIN protein [7]. ALADIN is involved in regulating multiple intracellular pathways such as signal transduction, nucleocytoplasmic transport, and transcription of RNA [8,9]. AS has an estimated prevalence of 1 in 1 million.…”
Section: Discussionmentioning
confidence: 99%
“…AS has an estimated prevalence of 1 in 1 million. However, it is suggested that the prevalence of this syndrome is inaccurate due to misdiagnosis and limited literature [8,9]. AS does not seem to be directly correlated with specific age, ethnicity, or sex and has varying degrees of severity on presentation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Les mêmes résultats sont retrouvés dans l'étude Tunisienne, le premier cas est similaire au notre et le deuxième présente une hypokaliémie et une activité rénine plasmatique pathologique [3]. Certains patients ne présentent l'insuffisance surrénalienne que tardivement au cours de l'évolution du SA [6]. L'achalasie est le troisième signe important du syndrome triple « A ».…”
Section: Discussionunclassified
“…Une étude publiée en 2018 [6] a rapporté des cas de syndrome triple « A » avec une atteinte neurologique sévère, y compris une tétraparésie spastique, une amyotrophie bulbo-spinale et une neuropathie périphérique motrice. Les auteurs ont conclu que dans ces cas, l'importance de l'amyotrophie fait partie du spectre neurologique phénotypique du syndrome et ont même suggéré de rajouter l'amyotrophie à l'éponyme.…”
Section: Discussionunclassified